2022
DOI: 10.3390/cancers14061413
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Resectable Gallbladder Cancer

Abstract: Gallbladder cancer (GBC) is the most common biliary tract cancer worldwide and its incidence has significant geographic variation. A unique combination of predisposing factors includes genetic predisposition, geographic distribution, female gender, chronic inflammation, and congenital developmental abnormalities. Today, incidental GBC is the most common presentation of resectable gallbladder cancer, and surgery (minimally invasive or open) remains the only curative treatment available. Encouragingly, there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 108 publications
0
14
0
2
Order By: Relevance
“…The three major clusters were surgery therapy, mechanism research-related study, and non-surgery therapy, representing the clinical research and basic research. Radical surgery remains the only curative treatment for resectable GBC ( 20 ). Since only 10% of patients have the opportunity of a radical resection, systemic therapy became an important subject of research ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The three major clusters were surgery therapy, mechanism research-related study, and non-surgery therapy, representing the clinical research and basic research. Radical surgery remains the only curative treatment for resectable GBC ( 20 ). Since only 10% of patients have the opportunity of a radical resection, systemic therapy became an important subject of research ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…An international multicentre study in 2015 showed that patients with T2h had higher vascular invasion, neural invasion, and lymph node metastasis than patients with T2p, and T2h were often associated with worse prognosis [13]. The gallbladder adjacent to the hepatic side has no serosal layer, there are as many as 20 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) gallbladder veins, and the tumour easily metastasises to the liver bed through the gallbladder veins [14]. RC was found in 31.4% of patients after index cholecystectomy, with the liver being the most common residual site.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical resection has an irreplaceable role in managing IGC, surgical treatment alone is unlikely to be su cient in patients with RC or stage III-IV disease, and systemic treatment has an important emerging role [15,16]. However, systematic reviews and meta-analyses pointed out that there is no strong evidence that adjuvant therapy is effective in GBC patients undergoing radical resection and only has some bene t in patients with positive lymph node disease, and positive surgical margins, or advanced disease [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical resection has an irreplaceable role in managing IGC, surgical treatment alone is unlikely to be sufficient in patients with RC or stage III-IV disease, and systemic treatment has an important emerging role [ 15 , 16 ]. However, systematic reviews and meta-analyses pointed out that there is no strong evidence that adjuvant therapy is effective in GBC patients undergoing radical resection and only has some benefit in patients with positive lymph node disease, and positive surgical margins, or advanced disease [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%